Decoding The Impact: How Corporate Structure And Size Influence Earning Response Coefficient - Rahmani, Hani Fitria; Mimin Ratna Sari (Politeknik Negeri Madiun, 2024)
The purpose of this research is to determine how much influence the capital structure and company size have on the earning response coefficient both size of the company on the earning response coefficient either partially or simultaneously on the Computer and Device Services Companies Listed on the Indonesia Stock Exchange for the period of 2020-2022.The research methods used in this research are descriptive methods and associative methods. In this research, the unit of analysis is the Financial Statement Document at the Computer and Device Services Company Financial Report Documents on Computer and Device Services Companies Listed on the Indonesia Stock Exchange for the period 2020-2022. The samples in this study were 36 annual financial reports annual. The analysis method uses panel data regression analysis. Based on the results showed that partially there is a significant positive effect of capital structure on earning response coefficient, and partially there is a significant positive effect of capital structure on earnings re capital structure on earning response coefficient, and partially there is a significant positive effect on earning response coefficient. significant effect of company size on earning response coefficient, and simultaneously there is an effect of capital structure and company size on earning response coefficient.